Tantangan Ryousai Kenbo dalam Menyeimbangkan Pekerjaan - Rima Novita Sari (Jurnal Bahasa Jepang Taiyou, 2021)
Ryousai kenbo created as country ideology to encourage women in Japan for not giving up their role as a mother. However, as the expansion of modernization, many opportunities for women to have career outside domestic roles are freely open. Today, ryousai kenbo could be considering as obstacle to aim women’s domestic role stability and social equality. The aim of the study is to identify the obstacle of balancing work life as ryousai kenbo and career women in Japan. This study is a qualitative approach by using analysis of article in media and survey. Theory is qualitative descriptive to find the analysis result. The method used is analysis of news article and survey. Based on the results, this study concludes the obstacle of women for work-life balance between ryousai kenbo and career women with four facts, which are 1) gender wages gap, 2) ryousai kenbo roles are limited to child rearing and house work, 3) mother as a career woman is facing difficult from resignation, 4) several regular regulations could not be implemented due to concerns of social pressure at work.